Business Communication in the Digital Age: Integration of Ethical Values and Islamic Teachings - Nofiyanti Nofiyanti; Andira Fajrin (International Journal of Management and Economic Research (IJOMER), 2025)
The development of digital technology has brought significant changes in business communication practices, creating new opportunities and challenges. In this context, ethics plays an important role as a moral foundation that directs business behavior to remain in accordance with human values and justice. This paper examines the urgency of applying ethics in digital business communication, especially in social media and e-commerce platforms, with an axiological approach and Islamic values. This study uses a literature-based qualitative method, examining the phenomenon of the spread of false information (hoak), manipulation of public opinion, and the challenges of maintaining corporate reputation in the digital space. The results of the discussion show that the application of communication ethics based on honesty, responsibility and integrity is the key to business success in the digital era. Islamic ethical values such as trustworthiness, justice, and transparency also have high relevance in shaping sustainable and dignified business communication. The conclusion of this paper emphasizes the importance of increasing digital literacy, strengthening regulations, and internalizing ethical values in every line of digital business communication in Indonesia.